EFEKTIVITAS KONTEN MEDIA SOSIAL INSTAGRAM @LAAKFKB TERHADAP PEMENUHAN KEBUTUHAN INFORMASI AKADEMIK MAHASISWA - Amila Nafila Vidyana (Commed Jurnal Komunikasi dan Media, 2023)
This research is motivated by the information needs of students regarding academic information, often students ask for the same and repeated academic information from each student, therefore laakfkb makes innovations to use Instagram social media as a medium for conveying information about academics to meet students' academic information needs so that students can get information in detail and quickly. With the aim of knowing how much influence the variable (X), namely the Effectiveness of Instagram Social Media Content @laakfkb on the variable (Y), namely Fulfillment of Student Academic Information Needs in this research. The research method in this study is quantitative to see the effectiveness of the variables used by researchers. researchers used data collection techniques using questionnaires. the subjects of this study were 100 students of the Faculty of Communication and Business Telkom University. the results of this study indicate that the content created by Instagram @laakfkb has been effective in meeting the information needs of its students. proven by one of the tests carried out, namely the hypothesis test, the results of which obtained data significance value of 0.000 <0.05. Based on the results of this data, it can be concluded that H0 is rejected and H1 is accepted. This means that the variable Effectiveness of social media content Instagram @laakfkb influences or is effective on the variable academic information needs of students. In conclusion, that Instagram content uploaded on Instagram @laakfkb is proven to be effective in meeting student information needs.